Facial Reconstruction following Mohs Micrographic Surgery: A Report of 622 Cases. Issue 4 (July 2014) - Grosfeld, Eline C.; Smit, Jeroen M.; Krekels, Gertruud A.; van Rappard, Julien H.A.; Hoogbergen, Maarten M.
Background: Around 100 to 200 patients undergo surgical reconstruction every year at our department of plastic and reconstructive surgery after Mohs micrographic surgery for nonmelanoma skin cancer. Objective: The aim of this report is to provide an overview of the type of facial reconstructions performed and investigate whether we achieved increased, definitive closure rates of the defect on the day of the excision after further improving the collaboration between the involved departments. Methods: All patients who underwent facial reconstruction at the Department of Plastic and Reconstructive Surgery following Mohs micrographic surgery between January 2006 and January 2011 were retrospectively systematically reviewed. Results: A total of 564 patients with 622 defects were identified. The different reconstructions used per aesthetic unit are described. The number of cases in which a reconstruction was performed on the same day as the resection significantly increased from 31 to 81% ( p < .001). Conclusion: Facial reconstruction following Mohs micrographic surgery is challenging. The type of reconstruction used depends on the type of defect and patient characteristics. A structured multidisciplinary approach improves the process from defect to reconstruction and can facilitate referrals.